THE ROLE OF COMMUNITY ORGANISATIONS IN PREVENTING BULLYING WITH CHILDREN (World Bulletin of Social Sciences, 2024)
Bullying is a pervasive problem affecting children globally, leading to significant emotional and psychological harm. While schools and families play crucial roles in prevention, the community can act as a vital support system. This article examines the role of community organizations in preventing bullying among children. The paper first defines bullying and explores its various forms, highlighting the impact on victims and the need for multifaceted interventions. It then analyzes the unique strengths of community organizations in addressing bullying, including their ability to provide early intervention, empowerment, parent education, community. The article further examines effective community-based programs and initiatives designed to prevent bullying, emphasizing the importance of collaboration between schools, families, and community organizations. It concludes by highlighting the critical role of community organizations in creating a positive and supportive environment where children can thrive and bullying is effectively addressed